IPhos, a new technique for the CALIFA CsI(Tl) calorimeter. (13th February 2015) - Bendel, M; Gernhäuser, R; Winkel, M; Alvarez-Pol, H; Cortina-Gil, D; Heiss, B; Henning, W F; Klenze, P; Bleis, T Le; Pfeffer, C; Pietras, B
Abstract: Within this paper we will present an entirely new energy reconstruction method iPhos for charged particles detected in CsI(Tl) crystals. Based on pulse shape analysis of CsI(Tl) scintillation signals [1] protons that cannot be stopped within the active detector material can be distinguished from those fully stopped. Due to a special signature of punch-through protons, they can be identified and their full energy is reconstructed from their specific energy loss. In a dedicated experiment at the Cyclotron Center Bronowice, Krakow the first proof of this method was achieved.